Investment Analysis of New Inpatient Wards Project at Ulin Hospital of Banjarmasin - Nugraha, Aldilla Wira; Aliludin, Arson (The Indonesian Journal of Business Administration, 2013)
Adequate health care in a province is one of the primary needs that cannot be neglected. These needs will affect the health and life expectancy of the population of the province. Hospital is one of the health facilities provided by the government or private, in which there are many types of health services one of which is the inpatient ward. The research for this thesis conducted at new inpatient wards project of BLUD Ulin hospital in Banjarmasin. At this time, RS Ulin has ten class inpatient services with a total capacity of 520 beds. The main focus of this thesis is to conduct an investment analysis on new inpatient wards which claimed a total investment cost of Rp. 39,781,562,180. Investment valuation method used is Net Present Value (NPV), Internal Rate of Return (IRR) and payback period (PBP). Alternative funding of this project is 100% through APBD or 60% debt of investment cost. From the analysis it was found that the value of the project by fully APBD funding alternative budget has a greater NPV and IRR and PBP faster the NPV is Rp 28,496,595,592; IRR 14.67%; simple PBP 7 years 5 months; discounted PBP 10 years 5 months while that for second alternative funding the NPV is Rp (1,504,304,542); IRR of 9.15%. The scenarios analysis are set to five scenarios, which are very pessimistic, pessimistic, mostly-like, optimistic, and very optimistic with their respective optimal occupancy rate 56%, 63%, 70%, 77%, and 84%. Under the very pessimistic scenario the project has NPV Rp 10,899,289,212; IRR 11.06%; simple PBP 8 years 2 months; PBP discounted 12 years 7 monthsÂ Keyword: Hospital, inpatient, BOR, NPV, IRR, PBP